Clinical Correlation Exercises 1-4 - Gabriel Virella (Association of American Medical Colleges, 2006)
Abstract These four clinical correlation exercises are designed to promote group learning with second-year medical students in an infection and immunity course. The cases were developed by a group of physicians with microbiology and infectious disease expertise. Students are divided into groups of four and provided with all four brief clinical case descriptions. From each description, students generate a differential diagnosis and have an opportunity to select tests and diagnostic procedures needed to refine their diagnosis. As the case progresses the students refine their differential diagnosis and respond to short-answer questions related to the pathophysiology. After the students have completed a case or the group of cases they receive a package with responses to the short-answer questions and a general commentary about each case to ensure all groups receive standard instruction. During the last 10 years of implementation, students have consistently shared that group-based learning is an optimal venue to promote understanding and retention of key facts and concepts.